1985
DOI: 10.1159/000149600
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Nucleic Acid of Rice Gall Dwarf Virus

Abstract: In negative stain preparations, the particles of rice gall dwarf virus (RGDV) had the form of angular icosahedra, approximately 65 nm in diameter, and resembled Phytoreovirus particles. The genomic double-stranded RNA of RGDV was fractionated by PAGE into 12 segments similar to those of the RNAs of the phytoreoviruses, wound tumor virus and rice dwarf virus, but of different mobilities. The RNAs were distinct from those of other plant reoviruses. RGDV therefore is confirmed as a new Phytoreovirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Sedi mentation was from left to right (ar row). from 0.5 x 10h to 2.7 x 106 [Omura et al, 1983;Kawano et al, 1984;Boccardo and Milne, 1985], We have reported that RRSV particles have polymerase activity [Uyeda et al, 1987], and we now describe the characteristics and products of this enzyme.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Sedi mentation was from left to right (ar row). from 0.5 x 10h to 2.7 x 106 [Omura et al, 1983;Kawano et al, 1984;Boccardo and Milne, 1985], We have reported that RRSV particles have polymerase activity [Uyeda et al, 1987], and we now describe the characteristics and products of this enzyme.…”
Section: Introductionmentioning
confidence: 66%
“…4). The Mr o f the RNAs, using tobacco mosaic virus (2.0-2.1 x 106), MS-2 phage (1.24 x 106), Escherichia coli 23S (1.0 x I04) and 16S (0.53 x 106) RNAs as stan dards, were estimated to be about half (or slightly larger) of those reported for the genomic dsRNAs [Kawano et al, 1984;Boccardo and Milne, 1985]. The 32P-labeled RNA segments 1-4, 7 and 8, and 9 and 10 were not resolved and appeared as single bands.…”
Section: Analysis O F the Rnas Synthesized In Vitromentioning
confidence: 99%
“…Genomic dsRNAs from rice gall dwarf virus (RGDV), rice dwarf virus (RDV) (both of subgroup I), MRDV and Fiji disease virus (FDV) (both of subgroup II), and rice ragged stunt virus (RRSV) (subgroup liD, all from the collection of this Institute (Boccardo et at., 1985), were denatured and electrophoresed by the same method. RNAs were then transferred overnight to nitrocellulose membranes, and treated as above for dot blots.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular sizes cal culated for RRSV RNAs ranged from 0.60 x 10fc to 2.98 x 106 daltons, with a total of about 18.15 x 106 daltons. For RRSV, values of the genome size ranging from 11.63 x 106 to 22.91 x 106 have been reported [7,10,13,23,24].…”
Section: Segmentation O F the Viral Genomementioning
confidence: 99%